EVALUATING THE EFFECTIVENESS OF TELEMEDICINE IN MANAGING CHRONIC DISEASE: A FOCUS ON HYPERTENSION AND DIABETES - Zubair Danish; Naila Javed; Sumbul Aqeeq; Chaudhary Ammar Bashir; Naseema Bano; Momina Qadir (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Regions with minimal access to healthcare facilities face continuing public health dangers from hypertension and diabetes mellitus diseases. Telemedicine has proven itself as a valuable healthcare tool which boosts medical services alongside patient monitoring especially for treating ongoing illnesses. Aim: The research evaluated the successful implementation of telemedicine technology for hypertension and diabetes management by measuring both patient care results and satisfaction together with protocol treatment compliance. Methods: The investigators conducted the prospective observational study at Ayub Medical Hospital Abbottabad which covered two years starting from February 2024 to January 2025. The research enrolled 100 patients who received either hypertension or diabetes or combined diagnoses. The participants obtained standard telehealth consultations as well as digital disease tracking and long-distance follow-up care services. Basel challenge readings together with blood pressure and blood glucose levels got documented and their changes tracked across the study duration. The questionnaires provided a methodology for evaluating both patient satisfactions along with their compliance levels. Results: The research project found substantial advancements in medical outcome results. A total of 72% of hypertensive patients reached controlled blood pressure goals during the research period although only 38% were at this level initially. The proportion of diabetic patients who maintained target fasting blood glucose increased to 68% while the initial figure was only 35%. Patient satisfaction stood high regarding telemedicine services as patients found convenience together with timely communication and reduced travel costs to be the main advantages. A majority of 76% of participants demonstrated greater drug compliance throughout the research period. Conclusion: Telemedicine demonstrated its worth as a successful approach to treatment administration of hypertension alongside diabetes. Telemedicine enabled improved disease management while enhancing patient medicine following and bringing better satisfaction. Results confirm that telemedicine should be employed as a standard approach for managing chronic diseases when serving patients in remote locations.